Knowledge, attitude, and practice about plagiarism among dental interns and postgraduate dental students in Riyadh city, Kingdom of Saudi Arabia - Alzahrani, Muaath Salem; Ingle, Navin Anand; Assery, Mansour K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Student’s involvements in research activities are becoming more and more common in the current academic scenario. Both undergraduate and postgraduate are given responsibility to involve in the research activities from beginning of their student academic year. Though many universities are involving students in these activities as part of their curricular activities, training of the students to be done appropriately in such a way that every part of the research activities including research or scientific misconduct to be well informed and discussed. Methods: A cross-sectional survey was conducted among a sample of 200 dental interns and postgraduate dental students in Riyadh Elm University. Validated questionnaire was utilised which had four sections as follows: (a) demographics (b) nine questions related to knowledge of plagiarism (c) twelve questions related to positive attitude toward plagiarism and; seven questions related to negative attitude toward plagiarism; and (d) eight questions related to practice of committing plagiarism. Data was analysed using the SPSS IBM software version 23. Results: Although majority (82.6%) have heard about plagiarism, only 50.6% were familiar with instances and 45.3% were familiar with penalty of plagiarism. There is a statistically significant association between all positive attitude items and education level (p<0.05) except one. Interns showed more positive attitude and less negative attitude as compared to postgraduates. Conclusions: Though the study shows some relevant and basic knowledge among the subjects of the study, in-depth of the topic is required for the subjects so that they publish with the great pride.